2016
DOI: 10.1101/045427
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Forward genetics by sequencing EMS variation induced inbred lines

Abstract: In order to leverage novel sequencing techniques for cloning genes in eukaryotic organisms with complex genomes, the false positive rate of variant discovery must be controlled for by experimental design and informatics. We sequenced five lines from three pedigrees of EMS mutagenized Sorghum bicolor, including a pedigree segregating a recessive dwarf mutant. Comparing the sequences of the lines, we were able to identify and eliminate error prone positions. One genomic region contained EMS mutant alleles in dwa… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…The highest and lowest number of mutations was observed in the B and D sub-genomes respectively, for both the mutant lines. It has been reported that the number of polymorphisms in a mutagenized genome may scale with overall genome size [35]. Among the three sub-genomes of wheat, the order of genome size is B (5.180 Gb) > A (4.935 Gb) > D (3.951 Gb) [36].…”
Section: Discussionmentioning
confidence: 99%
“…The highest and lowest number of mutations was observed in the B and D sub-genomes respectively, for both the mutant lines. It has been reported that the number of polymorphisms in a mutagenized genome may scale with overall genome size [35]. Among the three sub-genomes of wheat, the order of genome size is B (5.180 Gb) > A (4.935 Gb) > D (3.951 Gb) [36].…”
Section: Discussionmentioning
confidence: 99%
“…Given the ploidy level of C. quinoa, 2n = 4x = 36, and the genome size of 1.39 Gb (Jarvis et al, 2017), the rate of mutation, 1/203 kb, obtained in the current study would probably achieve approximately 6847 mutations throughout the whole genome of quinoa. Despite the high capacity to generate mutations in the genome, it is thought that the polyploidy of quinoa allows it to remain viable despite a high level of mutation (Martín et al, 2009) and the genome's coding capacity determines the phenotypically effective mutational target (Addo-Quaye et al, 2017). These criteria should be considered when new quinoa mutagenesis protocols are developed.…”
Section: Discussionmentioning
confidence: 99%
“…TILLING is an efficient reverse genetics approach for detecting induced mutations in pools of individuals. Combined with the NGS technologies, and the resolving power of overlapping pool design, TILLING provides an efficient and economical platform for functional genomics across thousands of organisms (Addo-Quaye et al, 2017), independently of the genome size, ploidy and reproductive system of plants (Rashid et al, 2011). Although TILLING is most powerful when applied to crops for which whole-genome sequences are available, it can be applied to target genes in any crop, provided that the sequence of the target gene itself is known in the target genome (Kumar et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…However, each of these approaches involved preceding backcrossing programs or analysis of large numbers of F 2 individuals for the assembly of bulks. Addo-Quaye et al (2017) omitted backcrossing and sequenced pools of Sorghum bicolor EMS mutant and wild-type individuals to filter for homozygous SNPs causing non-synonymous amino acid exchanges in the mutant population and could identify a recessive mutation. Although they were able to find a homozygous SNP in a protein-coding region their approach potentially missed mutations not caused by SNPs like insertions or deletions and would furthermore not have enough discriminative power to detect mutations in a heterozygous state, which is relevant for homozygous lethal alleles.…”
Section: Introductionmentioning
confidence: 99%